Studi Hadis Pendidikan di Perguruan Tinggi: Realitas, Problematika dan Solusi - Amrulloh, Amrulloh; Solichin, Mujianto (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2018)
This research is motivated by a number of discrepancies between the reality of educational h}adi>th quotation and the standard of the hadith quotation of the hadith. These divergences include the differences in the reference to educational hadith, assessment and process of understanding. This study aims to explain the motivation behind the citation of the educational hadith; classifying forms of educational hadith references, managing the validity of the educational hadith, categorizing the process of understanding the hadith; identifying the problems faced by educational hadith quoters, and then submitting the solution. This research applies integrative design between field research and library research. This study argues that the background of the educational hadith quotation revolves around the belief in the relevance between hadith and education; there are many discrepancies between the reality of the educational hadith quotation and the standard excerpt of the hadith; the problem of the educational hadith citation revolves around the ignorance of the hadith sciences and the difficulty of access to the primary reference to the hadith. This article then offers a solution that is to use the digital library of the hadith.